NOVEL MAGNETISM IN SPIN GAP SYSTEM - Hidekazu TANAKA (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2003)
Most of magnetic properties of conventional magnets can be understood in terms of the classical vector spin model. However, recent development of new quantum magnets and high-ﬁeld experiments at low temperatures revealed that some systems exhibit many- body effects characteristic of quantum particle system. Such behavior can be observed in spin dimer system, where pairs of ions with spin S=l/2 are coupled antiferromagnetically to form non magnetic singlet state at low temperatures.